Seasonal onychomadesis in an elderly gentleman - Supriya Venugopal; Dedee Frances Murrell (PAGEPress Publications, 2010)
A 79-year-old man with a history of dementia and hypertension initially presented with a ten year history of Beau's lines and seasonal nail shedding of his fingernails only. He denied any exposure to heavy metals, unusual activities or food. He stated that the seasonal nail shedding had been occurring for the last 5-10 years. On examination, six out of ten fingernails had been affected. He had significant toenail dystrophy. Fungal cultures and PAS staining of the toenails were negative. Routine serum biochemistry and haematology results were normal. Serum arsenic, cadmium and lead levels were also normal. Vitamin B12, zinc, folate, iron studies, thyroid function studies and homocysteine levels were also normal. Rheumatoid factor and anti-cyclic citrullinated peptide antibody antibodies were negative. Bilateral hand X-ray showed osteoarthritic change and did not show any features of psoriatic arthropathy. We discuss the case of a 79-year-old man with seasonal nail shedding, curiously affecting his fingernails only.